KEMITRAAN DALAM PENDIDIKAN ANAK USIA DINI (Analisis terhadap Pola dan Tingkah Laku Anak Usia Dini dan Lingkungan) - Anwar Hafidzi; Hadisa Putri (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2018)
Abstract: Partnership is a cooperative relationship between several parties in achieving a certain work relationship. The partnership between the school and the family and community in building an educational ecosystem is in line with the Ministry of Education and Culture's vision of